1996
DOI: 10.1111/j.1096-3642.1996.tb02189.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of myliobatoid elasmobranchs: with emphasis on the phylogeny and historical biogeography of neotropical freshwater stingrays (Potamotrygonidae: Rajiformes)

Abstract: The neotropical freshwater family Potamotrygonidae appears to be the only stingray group that has radiated in a non‐marine environment. To assess the affinities of potamotrygonids to other rays, a phylogenetic analysis was undertaken using 39 morphological characters from 18 stingray groups. The single tree produced (CI = 0.80, RI = 0.88) suggests that neotropical freshwater rays are a monophyletic group, and that within Potamotrygonidae, Paratrygon is basal to a clade composed of Plesiotrygon and Potamotrygon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
180
7
53

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(254 citation statements)
references
References 57 publications
14
180
7
53
Order By: Relevance
“…Fossil, morphological and molecular data support the hypothesis that mobulids are one of the most derived groups of elasmobranchs and closely related to rhinopterids (cownose rays, genus Rhinoptera) within a polyphyletic clade of Myliobatidae Aschliman et al, 2012a;Claeson et al, 2010;De Carvalho et al, 2004;Dunn et al, 2003;Lovejoy, 1996;McEachran and Aschliman, 2004;McEachran et al, 1996;Nishida, 1990;Shirai, 1996). However, a sister-clade relationship to a myliobatid-rhinopterid clade has also been proposed (Gonzalez-Isais and Dominguez, 2004) solely based on morphological data.…”
mentioning
confidence: 75%
“…Fossil, morphological and molecular data support the hypothesis that mobulids are one of the most derived groups of elasmobranchs and closely related to rhinopterids (cownose rays, genus Rhinoptera) within a polyphyletic clade of Myliobatidae Aschliman et al, 2012a;Claeson et al, 2010;De Carvalho et al, 2004;Dunn et al, 2003;Lovejoy, 1996;McEachran and Aschliman, 2004;McEachran et al, 1996;Nishida, 1990;Shirai, 1996). However, a sister-clade relationship to a myliobatid-rhinopterid clade has also been proposed (Gonzalez-Isais and Dominguez, 2004) solely based on morphological data.…”
mentioning
confidence: 75%
“…Initial phylogenetic studies of Rosa (1985), Lovejoy (1996), Lovejoy et al (1998), andMarques (2000) aimed to test the monophyly of this family, to infer the phylogenetic relationships among its three described genera, and to establish its sister group. These studies supported the monophyly of the Potamotrygonidae and most of them concluded that colonization of fresh water in South America is the result of a single colonization event.…”
Section: Discussionmentioning
confidence: 99%
“…As outgroup, we included the shark Heterodontus francisci (GenBank# AJ310141), and the Myliobatiformes stingray species Hexatrygon bickelli (GenBank# AY597334), and Himantura pacifica. The genus Himantura is considered the most likely sister taxon of Potamotrygonidae (Lovejoy, 1996;McEachran et al, 1996;Lovejoy et al, 1998;Dunn et al, 2003).…”
Section: Sampling Of Taxamentioning
confidence: 99%
“…The family Potamotrygonidae (Elasmobranchii: Myliobatiformes) is the only living chondrichthyan family restricted to freshwater habitats (Lovejoy, 1996) and they are distributed throughout most of the major river systems of South America. The Amazon Basin contains the greatest number of valid species of freshwater stingrays and Brazil is the country with the highest diversity of species (approximately 18 species) (Rosa, 1985;Compagno & Cook, 1995;Charvet-Almeida et al, 2002;Carvalho et al, 2003).…”
Section: Introductionmentioning
confidence: 99%